Determinan Perilaku Ibu Hamil dalam Melakukan Pemeriksaan Kehamilan pada Masa Pandemi Covid-19 - Melati Puspita Sari; Ririn Handayani (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
ANC or antenatal care can be interpreted the service of the mummy and fetus during pregnancy. Through pregnancy check, various advice and education related to gestation and preparation for birth can be given to mothers as early as possible. At this time of the Covid-19 pandemic, there were some who closed their PMB but 72% were still actively providing services by referring to the health protocols that had been established so as to prevent transmission, especially to pregnant women. This research including an analytical survey research. The population taken at PMB Ny. M Tamansari Village, Mumbulsari District with the amount of 3rd trimester expectant mother who came for a pregnancy checkup in April-July 2021 to the tune of 40 expectant mother, with technique sampling is total sampling. The research results obtained that was used Chi Square analysis represented that P value <0.05 was a significant relationship between the behavior of expectant mother doing ANC with Age, Education, Knowledge, Attitudes, Husband's Support and Health Facilities, the unrelated variable was the mother’s occupation. Present condition does not a barrier of expectant mother from pregnancy check-ups.